Parametric Architectural Design for a New City Identity: Materials, Environments and New Applications - Inès Sahtout Gaha (Journal of Contemporary Urban Affairs, 2023)
In contemporary architectural Design, we speak of a parametric structural design. A design that integrates new functionalities crossed with the spatial geometry of objects. It has been considered structured because it optimizes combinations that integrate a minimum of materials and data to respond to functions, uses, and needs more adapted to a society in perpetual evolution. Parametric modelling allows the usability of new materials and the integration of new structures in a variety of design environments. This transdisciplinary research explores aspects of parametric modelling, a design method that creates digital models using algorithms and parameters. By focusing on the material and immaterial plurality of the designed space, this method enables the generation of complex and innovative forms that would be difficult to realize with traditional methods. Then, from a position that redefines the city as both a "medium" city and an "object" city, we explore the fields of application and novelties that are investing in the fields of architectural construction. We examine how parametric modelling can be used to create more sustainable and environmentally efficient buildings, using parametric processes, and optimizing the use of space. In this sense, our research will lead us to identify two aspects of parametric modelling: the conceptual parametric design aspect and the constructive parametric design aspect. Finally, the results of our research enable us to identify a design process that demonstrates the feasibility of using parametric modelling to generate viable, sustainable, and versatile spaces.